Manajemen Laba dengan Pendekatan Abnormal Cash Flow, Abnormal Production Cost dan Abnormal Discretinary Expense (Studi Empiris pada Jakarta Islamic Index) - Suhesti Ningsih (Jurnal Ilmiah Ekonomi Islam, 2016)
Real earnings management is profit management through real activities of the company. Real earnings management is done by using three approaches, namely abnormal operations cash flow (Abn. CFO), abnormal production costs Abn. PROD), and abnormal discretionary expenses (abn DISCR). Abnormal values measured from the activity of the activities of each deviation between the actual value and the value of the activity expected activity. From the results of research on the company that is indexed in JII shows that real earnings management is performed through three approaches with different trends in each year. This is evidenced in 2008 real earnings management tends to be done through Abn DISC, 2009 through Abn approach CFO and 2010 through Abn PROD. Keywords: Abnormal CFO, Abnormal PROD, Abnormal   DISCR.JII Index.